If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2w)(x + -6w) = 0 Reorder the terms: (-2w + 3x)(x + -6w) = 0 Reorder the terms: (-2w + 3x)(-6w + x) = 0 Multiply (-2w + 3x) * (-6w + x) (-2w * (-6w + x) + 3x * (-6w + x)) = 0 ((-6w * -2w + x * -2w) + 3x * (-6w + x)) = 0 Reorder the terms: ((-2wx + 12w2) + 3x * (-6w + x)) = 0 ((-2wx + 12w2) + 3x * (-6w + x)) = 0 (-2wx + 12w2 + (-6w * 3x + x * 3x)) = 0 (-2wx + 12w2 + (-18wx + 3x2)) = 0 Reorder the terms: (-2wx + -18wx + 12w2 + 3x2) = 0 Combine like terms: -2wx + -18wx = -20wx (-20wx + 12w2 + 3x2) = 0 Solving -20wx + 12w2 + 3x2 = 0 Solving for variable 'w'. Factor a trinomial. (2w + -3x)(6w + -1x) = 0Subproblem 1
Set the factor '(2w + -3x)' equal to zero and attempt to solve: Simplifying 2w + -3x = 0 Solving 2w + -3x = 0 Move all terms containing w to the left, all other terms to the right. Add '3x' to each side of the equation. 2w + -3x + 3x = 0 + 3x Combine like terms: -3x + 3x = 0 2w + 0 = 0 + 3x 2w = 0 + 3x Remove the zero: 2w = 3x Divide each side by '2'. w = 1.5x Simplifying w = 1.5xSubproblem 2
Set the factor '(6w + -1x)' equal to zero and attempt to solve: Simplifying 6w + -1x = 0 Solving 6w + -1x = 0 Move all terms containing w to the left, all other terms to the right. Add 'x' to each side of the equation. 6w + -1x + x = 0 + x Combine like terms: -1x + x = 0 6w + 0 = 0 + x 6w = 0 + x Remove the zero: 6w = x Divide each side by '6'. w = 0.1666666667x Simplifying w = 0.1666666667xSolution
w = {1.5x, 0.1666666667x}
| 180=11x | | x^2-45x=4050 | | 180=4x | | ln(x-8)-ln(x+9)=ln(x-7)-ln(x+1) | | 150+(225*3.50)=2000 | | .25(j-8)=0.5j+2 | | 4(2a-4)=40 | | 4m-18m=112 | | 5-3x-21=4-2x-8 | | 10m-8(m+9)=88 | | y-1.34=9.89 | | 1-6x+5x=7 | | 7x-34x-48=0 | | 3n+15n=72 | | 2+(9-8)-34-6=22 | | X+(-17)+x+(-23)+2x=180 | | 3x+4(k-2)=4+x | | x^2-45=4050 | | (4x+5)+(5x-30)=180 | | 3x^3+3x^2=36 | | 5*2-13= | | 6(3y-12)=2(4y-5)+10y-8 | | x+0.32=0.45(x+9) | | 10x-2(x+3)=10 | | -3x+2=7x | | 7(4x-7)=2(14x+6) | | 2x-10=4x+8 | | 6x^2y+3x-9xy= | | 3.40x+2.80y=7.5 | | 9(2k+3)+2=11(k-1) | | 4-2.50-39.00=p | | 5times-8=12 |